Advances in the utilisation of carbon-neutral technologies for a sustainable tomorrow: A critical review and the path forward. (November 2022) - Nayak, Sneha; Goveas, Louella Concepta; Selvaraj, Raja; Vinayagam, Ramesh; Manickam, Sivakumar
Graphical abstract: Highlights: The eminence of lowering carbon footprint to mitigate climate change. Application of lignocellulosic biomass, microorganisms and algae in bio-energy generation. Carbon capture and sequestration by novel MOFs, MXenes and nanocomposites. Acumen in achieving Sustainable Development Goals through the implementation of the Clean Development Mechanism. Abstract: Global industrialisation and overexploitation of fossil fuels significantly impact greenhouse gas emissions, resulting in global warming and other environmental problems. Hence, investigations on capturing, storing, and utilising atmospheric CO2 create novel technologies. Few microorganisms, microalgae, and macroalgae utilise atmospheric CO2 for their growth and reduce atmospheric CO2 levels. Activated carbon and biochar from biomasses also capture CO2 . Nanomaterials such as metallic oxides, metal-organic frameworks, and MXenes illustrate outstanding adsorption characteristics, and convert CO2 to carbon-neutral fuels, creating a balance between CO2 production and elimination, thus zeroing the carbon footprint. The need for a paradigm shift from fossil fuels and promising technologies on renewable energies, carbon capture mechanisms, and carbon sequestration techniques that help reduce CO2 emissions for a better tomorrow are reviewed to achieve the world's sustainable development goals. The challenges and possible solutions with future perspectives are also discussed.